Mitigation of efflorescence of alkali-activated slag mortars by incorporating calcium hydroxide. (6th September 2021) - Tang, Desha; Yang, Changhui; Li, Xinyuan; Zhu, Xiaohong; Yang, Kai; Yu, Linwen
Highlights: Ca(OH)2 reduced the efflorescence extent of alkali-activated slag(AAS) mortar. The mitigation mechanism of Ca(OH)2 on the efflorescence of AAS mortar was analyzed. Ca(OH)2 decreased the permeability and ion leaching capacity of AAS. The mechanical properties of AAS mortar were enhanced by addition of Ca(OH)2 . Abstract: Due to the high alkali concentration, weak binding of Na + and relatively open microstructure, the efflorescence of alkali-activated slag (AAS) cement is a critical barrier limiting its widespread application. To reduce the efflorescence, Ca(OH)2 was added as a Ca-rich precursor into the binder with the dosage of 3, 6 and 9 wt% by slag. The efflorescence of AAS mortars was identified by visual inspection and mass weighing of efflorescence products formed on the surfaces of the mortar. Capillary porosity, water absorption rate, Na + leaching test, XRD and TG analysis were also carried out to explain the change of microstructure and hydration products caused by the incorporation of Ca(OH)2 . The results revealed that the addition of Ca(OH)2 significantly reduced the coverage areas and the amount of efflorescence products. However, visual inspection results were not consistent with that of mass weighing of efflorescence products, ion leaching, etc. If the impact of efflorescence on microstructure should be considered, visual inspection is not suitable. It can be concluded that the addition of Ca(OH)2 can mitigate the efflorescence by following reasons: firstly, the capillary porosity decreased from 16.86% to 15.22% and the water absorption rate decreased from 0.0366 mm/s 1/2 to 0.0179 mm/s 1/2 by adding 9% Ca(OH)2, which means that the migration pathway of the Na + and water within the mortar was decreased. Secondly, the leaching results indicated that fewer Na + leached from the Ca(OH)2 -added samples, either from powder leaching or block leaching, which means that the addition of Ca(OH)2 may enhance the binding of Na + by hydration products through increasing the C-A-S-H gel content.